On the status of so-called “double” monasteries in Byzantine Empire of the 4th — 6th centuries - Anna Vankova (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
In the early Byzantine Empire (4th — 6th cc.), besides (male) monasteries and (female) convents, there were certain variants of coexistence of monastic communities for men and women. The aim of this paper is to analyse data from the relevant sources and clarify what the term dipla monasteria referred to and whether it was equivalent to the concept of “double monasteries” in modern historiography as well as to introduce the concept twin-monasteries. The article also raises the question if there were changes in the number of such monasteries and if this depended on the geographical location of the community. The sources for this study are a broad range of texts, namely Justinian’s laws; canons of church councils; patristic works (Gregory of Nyssa, Gregory of Nazianzus, Basil the Great); hagiographic literature. The article comes to the conclusion that dipla monasteria referred to mixed monasteries. However, there was a range of variants of coexistence of men’s and women’s monastic communities. The sources contain information about double monasteries and twinmonasteries. Double ans mixed monasteries were mostly spread in Asia Minor of the 4th century, whereas in Byzantium on the whole other forms of monasticism prevailed.